SISTEM PENGOLAHAN DATA KEUANGAN PADA MADRASAH ALIYAH SWASTA MAHDALIYAH KOTA JAMBI - Yeniwati, Desi; Suana, Irma; -, Nilawati (LP2M Universitas Nurdin Hamzah, 2020)
School is a big activity where there are interrelated components. One important element that must be possessed by schools is optimal financial data processing. This research has produced a Financial Data Processing System in the Private City of Mahdaliyah Aliyah Madrasah City of Jambi, which is expected to be able to optimize the activities of financial data processing in the Private City of Aliyah Mahdaliyah Madrasah City of Jambi. This application was built using Visual Basic 6.0 tools and MySQL Database. The research method used is the waterfall method, as well as system modeling using Data Flow Diagram (DFD) modeling.